Genetic neurodegenerative diseases: the human illness and transgenic models. - Price, D.L.; Sisodia, S.S.; Borchelt, D.R. (Science, 1998)
Review The neurodegenerative disorders, a heterogeneous group of chronic progressive diseases, are among the most puzzling and devastating illnesses in medicine. Some of these disorders, such as Alzheimer's disease, amyotrophic lateral sclerosis, the prion diseases, and Parkinson's disease, can occur sporadically and, in some instances, are caused by inheritance of gene mutations. Huntington's disease is acquired in an entirely genetic manner. Transgenic mice that express disease-causing genes recapitulate many features of these diseases. This review provides an overview of transgenic mouse models of familial amyotrophic lateral sclerosis, familial Alzheimer's disease, and Huntington's disease and the emerging insights relevant to the underlying molecular mechanisms of these diseases.